The evolutionary and clinical implilcations of the uneven distribution of the frequency of the inherited haemoglobin variants over short geographical distances - Premawardhena,A; Allen,A; Piel,FBJ; Fisher,C; Perera,L; Rodrigo,R; Goonathilaka,G; Ramees,L; Peto,T; Olivieri,N; Weatherall,DJ (British Journal of Haematology, 2016)
Studies of the frequency of heterozygous carriers for common inheriteddiseases of haemoglobin in over 7500 adolescent children in 25 districts inSri Lanka have disclosed a highly significant variation over very short geo-graphical distances. A further analysis of these findings, including theirrelationship to the past frequency and distribution of malaria, climatic vari-ation, altitude, ethnic origin and consanguinity rates, have provided evi-dence regarding the evolutionary basis for the variable distribution of theseconditions over short distances. It is likely that the complex interplaybetween malaria and the environment, together with related ethnic andsocial issues, exists in many countries across the tropical belt. Hence, theseobservations emphasise the importance of micromapping heterozygote dis-tributions in high-frequency countries in order to define their true burdenand the facilities required for the prevention and management of thehomozygous and compound heterozygous disorders that result from theirinteraction.